Babesia bovis RON2 contains conserved B-cell epitopes that induce an invasion-blocking humoral immune response in immunized cattle - Mario Hidalgo-Ruiz; Carlos E. Suarez; Miguel A. Mercado-Uriostegui; Ruben Hernandez-Ortiz; Juan Alberto Ramos; Edelmira Galindo-Velasco; Gloria León-Ávila; José Manuel Hernández; Juan Mosqueda (Parasites & Vectors, 2018)
Abstract Background Babesia bovis belongs to the phylum Apicomplexa and is the major causal agent of bovine babesiosis, the most important veterinary disease transmitted by arthropods. In apicomplexan parasites, the interaction between AMA1 and RON2 is necessary for the invasion process, and it is a target for vaccine development. In B. bovis, the existence of AMA1 has already been reported; however, the presence of a homolog of RON2 is unknown. The aim of this study was to characterize RON2 in B. bovis. Results The B. bovis ron2 gene has a similar synteny with the orthologous gene in the B. bigemina genome. The entire ron2 gene was sequenced from different B. bovis strains showing > 99% similarity at the amino acid and nucleotide level among all the sequences obtained, including the characteristic CLAG domain for cytoadherence in the amino acid sequence, as is described in other Apicomplexa. The in silico transcription analysis showed similar levels of transcription between attenuated and virulent B. bovis strains, and expression of RON2 was confirmed by western blot in the B. bovis T3Bo virulent strain. Four conserved peptides, containing predicted B-cell epitopes in hydrophilic regions of the protein, were designed and chemically synthesized. The humoral immune response generated by the synthetic peptides was characterized in bovines, showing that anti-RON2 antibodies against peptides recognized intraerythrocytic merozoites of B. bovis. Only peptides P2 and P3 generated partially neutralizing antibodies that had an inhibitory effect of 28.10% and 21.42%, respectively, on the invasion process of B. bovis in bovine erythrocytes. Consistently, this effect is additive since inhibition increased to 42.09% when the antibodies were evaluated together. Finally, P2 and P3 peptides were also recognized by 83.33% and 87.77%, respectively, of naturally infected cattle from endemic areas. Conclusions The data support RON2 as a novel B. bovis vaccine candidate antigen that contains conserved B-cell epitopes that elicit partially neutralizing antibodies.